Association mapping for total phenols, total flavonoids and antioxidant activity in a Mesoamerican bean diversity panel - Nogueira, Alison Fernando; Moda-Cirino, Vânia; dos Santos Neto, José; Delfini, Jessica; Fagundes, Daniel Fernando Viana; Gepts, Paul; Gonçalves, Leandro Simões Azeredo (Frontiers in Agronomy, 2025)
Beans are highly important for food and nutritional security in several South America, Asia, and Africa countries. Exploiting this crop’s genetic diversity is essential for breeding programs’ success. The objective of this study was to identify genomic regions associated with total phenolic content (TPC), total flavonoid content (FLA), and antioxidant activity (DPPH) in common bean grains in a Mesoamerican bean diversity panel. Phenotypic data were collected from two locations (Research Stations of the Paraná Rural Development Institute IAPAR-EMATER – IDR-Paraná) in the municipalities of Londrina and Guarapuava, Paraná, Brazil, and were subjected to variance analysis, heritability estimation, as well as histogram, density distribution, and boxplot analyses to assess genetic progress for black and carioca cultivars. For the genotypic data, four multi-locus genome-wide association studies (GWAS) were conducted to detect significant QTNs for the target traits. All analyses were performed using the R software. Analysis of variance showed a significant effect of genotype and genotype × environment interaction (p<0.01) for all traits, while no significant effect was observed for the environment. Heritability ranged from 93.1% to 99.8%, indicating low influence of environmental variation. Significant correlations (p<0.01) were observed among the traits evaluated. After filtering the SNPs obtained via GBS, 25,011 high-quality SNPs were identified for the GWAS study. After removing SNPs with high linkage disequilibrium, 707 SNPs were retained for population structure analysis. In total, 147 unique QTNs were significant for the three biochemical traits studied (TPC, FLA, and DPPH), of which 41 were detected at least twice by one of the seven multi-locus methods used or in different environments analyzed (Londrina, Guarapuava, and LSmeans). Candidate genes linked to the biosynthesis of phenolic compounds and antioxidant activity were also identified, highlighting the genetic complexity of these traits.